The plethora of yields in property investment and finance: a summary. Issue 4 (6th July 2015) - French, Nick; Patrick, Michael
Abstract : Purpose: – The purpose of this paper is to provide a summary, with examples, of the various types of yields that are used as benchmarks in the UK for property and finance. Design/methodology/approach: – Simple examples explain the differences between the various benchmarks used for different assets. Findings: – The paper highlights the differences between the various benchmarks for different assets. Research limitations/implications: – This is an Education Briefing. Originality/value: – The paper provides a summary of the various types of yields that are used as benchmarks in the UK for property and finance.